(untitled) (Bioagro, 2020)
The use of biostimulants and biocontrollers in nurseries can favor the obtaining of high quality seedlings. The effect of the application of biostimulants with and without inoculation of Trichoderma harzianum on growth and development of passion fruit seedlings was evaluated. The trial was carried out in a farm located in Santiago Mariño municipality, Aragua State, Venezuela, using a completely randomized design with a 5x2 factorial arrangement and three repetitions. The factors were biostimulants (Terrahumus; Stimulant Plus Manvert; Biorend and Biovida activator, plus a control without product application) and Trichoderma harzianum (presence or absence) for a total of 10 treatments. The evaluated variables were leaf number (LN), plant height (PH), chlorophyll index (CI), root length (RL), shoot dry weight (SDW) and root dry weight (RDW). There was no interaction between the factors. The application of biostimulants exerted a positive effect on the biometric variables such as LN and RDW, with respect to the control. There were significant differences between the application of T. harzianum and the control, with increases of 23.75; 23.84; 12, 27; 88 and 64.3 % for LN, PH, RL, SDW and RDW, respectively. It is concluded that the use of stimulating substances and T. harzianum improves parameters related to growth and development in passion fruit seedlings.